An architecture and a method for web services design: towards the realisation of service-oriented computing. (5th September 2006) - Baghdadi, Youcef; Al-Rawahi, Najla Nasser
Service-Oriented Computing (SOC) is the computing paradigm that utilises services as fundamental building blocks. Currently, web services provide a standard-based realisation of SOC due to: (a) the machine-readable format (XML) of their specifications and (b) their messaging protocols built on top of the internet. However, their deployment is still hindered by some technical, semantic and methodological issues. This paper concerns an architecture that guides a methodology to identify, specify, design, organise, deploy and manage a sound and complete set of web services. First, the paper highlights what existing approaches, from both IT and business perspectives, have provided to web services with respect to the following: (1) architecture, (2) design process, (3) building blocks, (4) wrapping legacy (5) usage and reuse, (6) semantics, (7) quality factors and (8) organisation and management. Then a multiple abstraction level architecture is defined, composed of high layers to deal with business orientations and low layers to deal with IT. Finally, the architecture is used as a web services design methodology with respect to SOC.